Rendimentos do milho em resposta aos controles de plantas daninhas e da lagarta-do-cartucho - Lima, Marilene Santos de (2007)
Weeds and the fall armyworm can cause considerable corn yield losses. This study aimed to evaluate green ear yield and corn grain yield as a response to weed and fall armyworm control. A completely randomized block design with split-plots and five replicates was used. Corn cultivar AG 1051 was grown without weed control or with hoeings performed at 20 and 40 days after planting. Control of the pest (applied to the subplots) was performed with sprays of: water (control); deltamethrin (5 g active ingredient ha-1); neem oil, at 0.5% (diluted in water); and neem leaf extract at 5%. Each product was sprayed three times, at seven-day intervals, starting on day 7after planting, using 150 L ha-1. Green ear yield, grain yield, and most other characteristics evaluated were reduced due to the lack of weed control (27 predominant species). Pest control in the weeded plots did not influence green ear yield and grain yield, with the exception of green mass of marketable husked ears, which was reduced when the caterpillar was not controled. Without weed control, the extracts or deltamethrin sprays provided the highest yields in terms of characteristics used to evaluate green corn, except for husked ear mass. The best results for grain yield were obtained with deltamethrin and neem extract, respectively